PICES Press, Vol. 23, No. 1, Winter 2015 - North Pacific Marine Science Organization (PICES) (North Pacific Marine Science Organization (PICES), 2015)
PICES science in 2014: A note from the Science Board Chairman (pp. 1-5); 2014 PICES awards (pp. 6-8); Fisheries bycatch: Global issues and creative solutions (pp. 9-12); 2014 PICES Summer School: End-to-End models for marine resources management and research (pp. 13-17); Seabirds as early warning indicators of climate events in the Pacific (pp. 18-20); Japan launches a new, state-of-the-art training ship – the Oshoro Maru V (pp. 21-22); PICES calendar of events (pp. 23-23); Workshop W4 on “Networking ocean observatories around the North Pacific Ocean” (pp. 24-27); The impact of Japanese tsunami debris on North America (pp. 28-30); The state of the western North Pacific in the first half and warm season of 2014 (pp. 31-32); The Bering Sea: Current status and recent trends (pp. 33-35); The warm blob – Conditions in the northeastern Pacific Ocean (pp. 36-38); Changes in the Secretariat (pp. 39-46)